Modalità di collaborazione e ruolo pubblico dell’antropologia in una consulenza di ambito coreutico - Natali, Cristiana (Antropologia Pubblica, 2019)
In January 2017 I was involved as a consultant in the creation and elaboration of a project, promoted by Simona Bertozzi, an Italian contemporary dance choreographer, as part of the initiative MigrArti-performance. For this initiative, the Italian Ministry for Arts and Culture selected projects which mixed artistic forms including a «preparatory series of workshops with the participation and involvement of immigrants, especially of second generation young immigrants, in order to promote intercultural dialogue»1. The project involved the Tamil bharata natyam teacher Sharmini Kavithasan and people from the Associazione Unione dei Tamil d’Italia. The project won the 2017 MigrArti-performance award and in June-July 2017 the workshops took place. The participants were 16 children and young girls from Sri Lankan Tamil families living in different Italian towns. The workshops were carried out in Genoa and Bologna for a total of ten days. This paper illustrates the methods of collaboration with the commission and the impact of the project in terms of public anthropology.